SISTEM INFERENSI FUZZY MAMDANI UNTUK PENGHITUNGAN BONUS KARYAWAN PT. ABC - Sherly Andini; Maria Ulfah Siregar; Shofwatul Uyun; Nurochman Nurochman (JURNAL TEKNIK INFORMATIKA, 2021)
A bonus in a company is an appreciation of the company for its employees for their dedication to work. Giving the bonus is sometimes prone to subjektives, not relevant to work pertformance, and etc. This is also impelemented in PT. ABC, which rewards employees for their performance. The calculation of employee bonuses at PT. ABC still uses spreadsheet tool so that the results of calculating employee bonuses tend to be subjective and be human error in inputting complex formula. Therefore, to get the suitable employee bonus calculation results, PT. ABC requires a specific computer system for the employee bonus calculation. This research uses Fuzzy Inference System Mamdani method because Mamdani method is often used for fuzzy logic control problems and is accordance with the process of input of human information. In Mamdani method, there are four stages, namely the formation of fuzzy sets, application of implications function, composition of rules and defuzzyfication. Our Mamdani method was designed upon 27 rules which is likely adding complexity and temptation on human. Calculations on a system are tidier and more structureable rather than on spreadsheet tool. The system which is based on web could run almost everywhere as long as there is internet connection. The results of this study indicate that computer calculations result the same as manual calculations by hand. Functionality testing show that the system is functioning 100% and the system access test shows that 60% of respondents strongly agree and 40% of respondents agree with the ease of the system.